MATA SEHAT UNTUK MASA DEPAN CERAH : EDUKASI KESEHATAN MATA PADA REMAJA - Nona, Jenifer Pricillia; Langasa, Siti Aigina; Ngofangare, Sri Dessy S.M.; Bada, Wahdi; Lestari, Tutik (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Eye health is an important aspect of life that often gets less attention, especially among children and adolescents. In today's digital era, the use of electronic devices such as mobile phones, tablets, and computers has become an inseparable part of daily activities. The purpose of this activity is to increase awareness and knowledge about the importance of maintaining eye health from an early age. The counseling activity was carried out at the Faculty of Health Sciences which was attended by 15 students. A pre-test was given before the counseling took place, then continued with providing counseling about eye health using PPT media and continued with the provision of a post-test questionnaire. There was an increase in participant knowledge where the average pre-test score was 8.67 and after that it increased to 8.80. It is hoped that with this activity, participants can apply healthy habits in their daily lives.